2002
DOI: 10.1046/j.1365-2141.2002.03577.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose doxorubicin‐induced necrosis in Jurkat cells and its acceleration and conversion to apoptosis by antioxidants

Abstract: Summary. We treated rapidly growing Jurkat cells with 40 nmol/l of doxorubicin for 72 h. After 36 h, the G2‐arrested cells became larger and some of them started endoreplication. Nuclear staining with Hoechst 33342 combined with propidium iodide (PI) exclusion revealed that about 90% of the cells were necrotic at 72 h, although apoptotic cells accounted for only 8%. Incubation with 40 nmol/l of aclarubicin or cytosine β‐d‐arabinofuranoside for 60 h induced necrosis both in Jurkat and ml‐1 cells. Pre‐necrotic J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
(44 reference statements)
3
17
0
Order By: Relevance
“…We previously showed that treatment with 50 nM doxorubicin for 48 h induced necrosis in most Jurkat cells without apparent apoptosis (Sugimoto et al, 2002). In this study, addition of 100 nM GM at 24 h made more than 40% of doxorubicin-treated Jurkat cells TUNEL positive ( Figure 6a).…”
Section: Addition Of Geldanamycin Converted Doxorubicin-induced Necrosupporting
confidence: 58%
See 1 more Smart Citation
“…We previously showed that treatment with 50 nM doxorubicin for 48 h induced necrosis in most Jurkat cells without apparent apoptosis (Sugimoto et al, 2002). In this study, addition of 100 nM GM at 24 h made more than 40% of doxorubicin-treated Jurkat cells TUNEL positive ( Figure 6a).…”
Section: Addition Of Geldanamycin Converted Doxorubicin-induced Necrosupporting
confidence: 58%
“…Clonal cell culture Methylcellulose cell culture was carried out in a 35-mm suspension culture dish (Nalge Nunc, Rochester, NY, USA) using Methocult H4230 (Stem Cell Technologies, Vancouver, BC, Canada) essentially as described previously (Sugimoto et al, 2002). Rapidly growing Jurkat and HL-60 cells were treated with 50 nM doxorubicin or with 1.2 mM of ICRF-193 for 24 h, and further incubated in the presence or absence of 100 nM GM for additional 24 h. Then living cell numbers were counted by trypan blue exclusion test, and 1 Â 10 4 cells were plated for each condition as triplicate.…”
Section: Confocal Laser Microscopymentioning
confidence: 99%
“…Tempol potentiated the cell death and/or apoptosis, and upregulated p22 protein expression (Ravizza et al, 2004b) in Jurkat tumor cells (Sugimoto et al, 2002), human Burkitt lymphoma cells (Shacter et al, 2000) and colon cancer cells (Ravizza et al, 2004b). Tempol reduced ROS and diminished toxicity of the chemotherapeutic agents doxorubicin, cisplatin, AraC or VP-16 (Czepas et al, 2008).…”
Section: Additional Actions Of Tempolmentioning
confidence: 99%
“…Sugimoto et al (2002) also reported that low-dose of doxorubicin (40 nmol/L) induced 90% of necrosis and 8% of apoptosis in Jurkat cells. Furthermore, the percentages of apoptosis induction by fractions F2 and F4 are higher than F3 and F5.…”
Section: Apoptosis Induction On Hela Cells By Fractions Containing Cymentioning
confidence: 88%